Disinfection effect of chlorhexidine and castor oil based on usage time on the impact strength of denture base heat polymerized acrylic resin - Montahir, Reza Dimansyah Azis; Putri Welda Utami Ritonga (Indonesian Journal of Prosthodontic, 2024)
Heat polymerized acrylic resin is the most frequently used type of acrylic resin because it has several advantages. Heat polymerized acrylic resin dentures must be disinfected to maintain cleanliness and prevent diseases caused by wearing unclean dentures.. The chemical method is a good and easiest method to do by immersing the dentures in a disinfecting solution. The immersion will clean the surface of the denture and reach the undercut area of the denture. Chlorhexidine and castor oil are ingredients that have substances that can clean dentures, but the content in these materials has an influence on the properties of dentures, one of which is mechanical properties. This study aimed to know the effect of disinfection of chlorhexidine and castor oil based on time of use on the impact strength of heat polymerized acrylic resin denture bases with simulations of 3, 4, and 5 years. The sample was tested using a Charpy Impact Tester to determine the impact strength value. This study showed that there was an effect of castor oil on the impact strength of heat polymerized acrylic resin, but the change still above the minimum value, so this can be suggested as a disinfection material.